IMPLEMENTATION OF STATISTIC PROCESS CONTROL IN FLAT SHOES AND HIGH HEELS PRODUCTION PROCESS - Rinta Suhardi, Agatha; Silviani Marindra, Vina (International Journal of Psychosocial Rehabilitation, 2020)
The company implements quality control in order to improve the quality of products or services, increase productivity by reducing defective products, and anticipate mismatches in the production process so that the products produced are still in accordance with the standards and specifications set by the company. The purpose of this study is to identify factors and constraints that affect the process of controlling the quality of flat shoes and high-heeled products that are carried out by the company. The research method uses descriptive analysis through Pareto diagrams, causal diagrams, control maps p and map controls c. The results of data processing indicate that the company has made several efforts to suppress the defective products produced. Analysis using a control chart makes it easier to see the most dominant factors and constraints and will get the results that must be done by the company to suppress improper production processes.